2002
DOI: 10.1038/sj.bmt.1703769
|View full text |Cite
|
Sign up to set email alerts
|

G-CSF-primed haploidentical marrow transplantation without ex vivo T cell depletion: an excellent alternative for high-risk leukemia

Abstract: Summary:Based on our encouraging results of G-CSF-primed HLA-matched related marrow transplants for high-risk leukemia, we extended the study from matched related to haploidentical transplants using G-CSF primed marrow and sequential immunosuppressants to prevent both graft-versus-host disease (GVHD) and host-versusgraft rejection (HVGR). Fifteen high-risk leukemia patients, who needed urgent transplantation but lacked an HLA-matched donor, underwent G-CSF-primed haploidentical marrow transplantation without e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…Therefore, it was concluded that GBM from haploidentical-mismatched sibling donors can be an excellent alternative for the treatment of high-risk hematological patients lacking matched donors. 95 Similar conclusions were also reported for 45 patients with high-risk AML, who received unmanipulated GBM from haploidentical sibling donors. 96 …”
Section: Gbm From Hla-identical Sibling Donorssupporting
confidence: 71%
“…Therefore, it was concluded that GBM from haploidentical-mismatched sibling donors can be an excellent alternative for the treatment of high-risk hematological patients lacking matched donors. 95 Similar conclusions were also reported for 45 patients with high-risk AML, who received unmanipulated GBM from haploidentical sibling donors. 96 …”
Section: Gbm From Hla-identical Sibling Donorssupporting
confidence: 71%
“…18 The incidence of aGVHD was only 6.3% in G-BM transplants compared with 33% in steady-state marrow transplants. 19 (2) Mixtures of G-PB and G-BM have successfully introduced T-cell hyporesponsiveness, polarization of T cells from Th1 to Th2 and protected from aGVHD. 20 (4) Higher-dose stem cell numbers may be given via a combination of G-BM and G-PBSC than via BM or PB alone to overcome the harmful effect of ATG on hematopoiesis.…”
Section: Discussionmentioning
confidence: 99%
“…To promote rapid engraftment while avoiding detrimental chronic GVHD, several previous studies have investigated megadose SCT using pBM plus PBSCs 10 and high-dose pBM. 5,6,8,11 On the basis of these earlier studies, we investigated the use of pBM in allogeneic sibling SCT under less than optimal conditions. More specifically, we examined the effectiveness of this procedure in cases of inferior donor condition (that is, markedly lower body weight than the recipient) and in recipients exhibiting various clinical comorbidities.…”
Section: Introductionmentioning
confidence: 99%